Unveiling The Entrepreneurial Mindset: A Comparative Exploration Of Pancasila Economic Values And Islamic Principles - Pandikar, Andri Soemitra Ernandia; Disman, Disman; Sundawa, Dadang (International Journal of Economics Development Research (IJEDR), 2024)
This article presents a comparative exploration of the economic values of Pancasila and Islamic principles to reveal the entrepreneurial mindset. Exploring the synergy between Pancasila, the five foundations of the Indonesian state, and Rukun Islam, the five religious value systems, to build an Indonesian national education value system (Beck & Irawan, 2016). This research also aims to explain gender differences in entrepreneurial tendencies among Islamic economists, by emphasizing the role of gender in entrepreneurial initiatives in this context (Costa & Pita, 2021). Furthermore, this paper explores the three pillars of Islamic entrepreneurship that contribute to economic development: the entrepreneurial pillar, the ethical pillar, and the religious-spiritual pillar, which guides entrepreneurs to run their businesses based on Islamic principles and values (Basit & Mitra, 2023). . In addition, this research seeks to reveal how the entrepreneurial intentions of students studying at Islamic Universities differ, emphasizing the importance of accommodating entrepreneurial intentions through university policies and curricula (Hidayati et al., 2022). This paper provides a comprehensive exploration of the entrepreneurial mindset in the context of Pancasila economic values and Islamic principles, highlighting gender differences in entrepreneurial tendencies, university-based entrepreneurial activities, and the development of entrepreneurial initiatives through Islamic principles and values.